2021 Parliamentary elections in the Republic of Moldova – An attempt at post-election analysis - Macuhin, Alexandr (Eastern Review, 2021)
This article analyses the parliamentary elections held in the Republic of Moldova in 2021, as a result of which the right-wing party, formerly in opposition, won, and was able to form its own single-party government with a parliamentary majority, which has not happened in Moldova exactly 20 years – since 2001. In this article the basic positions of the “left” and “right” political camps in the Republic of Moldova before the elections are analysed; as well as the mechanics of the electoral campaign and the voting process in different socio-geographical profiles. In 2021 The Republic of Moldova, for the first time in many years, faced the phenomenon of “overturning elections”; understanding the mechanics of which contributes to the development of a much better political and electoral process in general. At the same time, despite the special nature of the 2021 elections, the electoral political process in the Republic of Moldova continues to show several fixed tendencies, such as the geographical polarization of Moldovan voters residing in the EU or Russia, and the overall objective decrease of interest in the electoral process in general, regardless of the degree of the political and social representation of the political parties represented in the elections.